Dinamika Hak Lintas Damai dalam Perspektif Indonesia - Mokhamad Gisa Vitrana; Syakhila Bella Maulidya (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
Territorial sovereignty of the States over the sea has an exceptional contra from several the big maritime States: can their ships sail over a territorial water of the states. The history of international society has created that the seas was open for the ships of all States even sailing in waters near the coast of the States without being bound by any law. Nowadays, unfortunately sailing activities are not unlimited, but those activities are assured with a Right of Innocent Passage which is regulated by several international laws, especially the 1982 United Nation on the Law of the Sea. Apparently, the implementation of the Right of Innocent Passage falls into different perspective of State Parties. Furthermore, Indonesia is one of the State Parties to the 1982 United Nation on the Law of the Sea that already has regulations regarding the Right of Innocent Passage. This article focuses on the development the Right of Innocent Passage from its early history of its formation, codification effort by the international society and its implementation in Indonesia law.